Risk Management in Customs Inspection of Goods - Федотов, Олексій Павлович; Федотов, О. П.; Федотов, Алексей Павлович; Fedotov, Oleksii P.; Зотенко, Оксана Олександрівна; Зотенко, О. О.; Зотенко, Оксана Александровна; Zotenko, Oksana O. (Одеса : Видавничий дім «Гельветика», 2020)
The article reveals the main applied aspects of the procedure of inspection of goods and commercial vehicles at the present stage of development of the customs sphere and the legislation of Ukraine on customs matters. In the context of legislative innovations and changes in customs practice, the authors highlight the basic aspects of the implementation of such principles of customs control as selectivity and minimization of customs control when checking the customs declaration for risk in the Automated Risk Management System. In addition, the authors highlighted the features of the choice of forms of customs control by the Automated Risk Management System. It is determined that the automatic system, which is a risk management system, does not perform the format-logical control (does not check the authenticity of consignment, shipping and commercial documents (their structural construction), does not check the authenticity of prints on the forms of these documents, etc.). In this case, the application or non-application of forms of customs control in case of failure of the risk management system (green) will be based on professional qualities and special principle stand of the customs official of the State Customs Service of Ukraine, which is authorized to conduct customs control and customs clearance of goods and vehicles of the commercial purpose under such customs declaration. Through the prism of the study of the provisions of the order of the Ministry of Finance of Ukraine dated May 29, 2012 № 623 “On approval of the Procedure for inspection and re-inspection of goods, commercial vehicles” it is concluded that some of its provisions regulate time standards (of the head of customs clearance and the declarant, the carrier) of the notification of the inspection of goods, commercial vehicles (“notorious” 10 minutes). It is proposed to change the time of notification (head of the customs clearance department and the declarant, the carrier) about the inspection of goods, commercial vehicles up to 30 minutes. It is noted that 10 minutes is not enough to analyze the forms of customs control generated by the risk management system, and sometimes even to study and understand the customs official of the State Customs Service of Ukraine, which is authorized to carry out customs control and customs clearance of goods, commercial vehicles for commercial purposes under the customs declaration.

У статті розкрито основні прикладні аспекти процедури огляду товарів та транспортних засобів комерційного призначення на сучасному етапі розвитку сфери митної справи та законодавства України з питань митної справи. Авторами у контексті законодавчих новацій та змін практики здійснення державної митної справи висвітлено базові аспекти реалізації таких принципів митного контролю як вибірковість та мінімізація митного контролю при перевірці митної декларації на предмет ризикованості в Автоматизованій системі управління ризиками. Крім того, авторами виокремлено особливості обрання форм митного контролю Автоматизованою системою управління ризиками. Встановлено, що автоматична система, якою є система управління ризиками, не здійснює формато-логічний контроль (не перевіряє автентичності товаротранспортних, товаросупровідних та комерційних документів (їх структурну побудову), не перевіряє достовірності відбитків печаток на бланках цих документів тощо). При цьому, застосування або незастосування форм митного контролю у випадку неспрацювання системи управління ризиками (зелений колір) буде здійснюватися, виходячи із професійних якостей та особливої принциповості посадової особи митниці Державної митної служби України, яку уповноважено на здійснення митного контролю та митного оформлення товарів, транспортних засобів комерційного призначення за такою митною декларацією. Через призму дослідження положень наказу Міністерства фінансів України від 29 травня 2012 р. № 623 “Про затвердження Порядку проведення огляду та переогляду товарів, транспортних засобів комерційного призначення” зроблено висновок про те, що окремі його положення регламентують часові нормативи повідомлення (керівника підрозділу митного оформлення та декларанта, перевізника) про проведення огляду товарів, транспортних засобів комерційного призначення (“горезвісні” 10 хвилин). Пропонується змінити час повідомлення (керівника підрозділу митного оформлення та декларанта, перевізника) про проведення огляду товарів, транспортних засобів комерційного призначення до 30 хвилин. Зазначається, що 10 хвилин вкрай недостатньо для аналізу згенерованих системою управління ризиками форм митного контролю, а іноді навіть для їх вивчення та усвідомлення посадовою особою митниці Державної митної служби України, яка є уповноваженою на здійснення митного контролю та митного оформлення товарів, транспортних засобів комерційного призначення за митною декларацією.

В статье раскрыты основные прикладные аспекты процедуры досмотра товаров и транспортных средств коммерческого назначения на современном этапе развития сферы таможенного дела и законодательства Украины по вопросам таможенного дела. Авторами в контексте законодательных новаций и изменений практики осуществления таможенного дела освещены базовые аспекты реализации таких принципов таможенного контроля как избирательность и минимизация таможенного контроля при проверке таможенной декларации на предмет рискованности в Автоматизированной системе управления рисками. Кроме того, авторами выделены особенности избрания форм таможенного контроля Автоматизированной системой управления рисками. Установлено, что автоматическая система, которой является система управления рисками, не осуществляет формато-логический контроль (не проверяет подлинности товаротранспортных, товаросопроводительных и коммерческих документов (их структурное построение), не проверяет подлинности оттисков печатей на бланках этих документов и т.п.). При этом, применение или неприменение форм таможенного контроля в случае срабатывания системы управления рисками (зеленый цвет) будет осуществляться, исходя из профессиональных качеств и особой принципиальности должностного лица таможни Государственной таможенной службы Украины, уполномоченного на осуществление таможенного контроля и таможенного оформления товаров, транспортных средств коммерческого назначения по такой таможенной декларации. Через призму исследования положений приказа Министерства финансов Украины от 29 мая 2012 г. № 623 “Об утверждении Порядка проведения осмотра и досмотра товаров, транспортных средств коммерческого назначения” сделан вывод о том, что отдельные его положения регламентируют временные нормативы уведомления (руководителя подразделения таможенного оформления и декларанта, перевозчика) о проведении досмотра товаров, транспортных средств коммерческого назначения (“пресловутые” 10 минут). Предлагается изменить время уведомления (руководителя подразделения таможенного оформления и декларанта, перевозчика) о проведении досмотра товаров, транспортных средств коммерческого назначения до 30 минут. Отмечается, что 10 минут крайне недостаточно для анализа сгенерированных системой управления рисками форм таможенного контроля, а иногда даже для их изучения и осознания должностным лицом таможни Государственной таможенной службы Украины, уполномоченным на осуществление таможенного контроля и таможенного оформления товаров, транспортных средств коммерческого назначения по таможенной декларации.
Fedotov O., Zotenko O. Risk Management in Customs Inspection of Goods / О. Fedotov, O. Zotenko // Lex Portus : юрид. наук. журн. / редкол. : С. В. Ківалов (голов. ред. ради), Б. А. Кормич (голов. ред.), Т. В. Аверочкіна (наук. ред., відп. секр.) [та ін.]; НУ "ОЮА", ГО "МА Святий Миколай". – Вип. 3 (23). – Одеса : Видавничий дім «Гельветика», 2020. – С. 79–94.
Keywords: forms of customs control; customs formalities; risk management system; customs clearance; customs declaration; indication of the results of automatic verification of the customs declaration; форми митного контролю; митні формальності; система управління ризиками; митне оформлення; митна декларація; індикація результатів автоматичної перевірки митної декларації; формы таможенного контроля; таможенные формальности; система управления рисками; таможенное оформление; таможенная декларация; индикация результатов автоматической проверки таможенной декларации; Research Subject Categories::LAW/JURISPRUDENCE